1996
DOI: 10.1016/s0006-8993(96)01041-4
|View full text |Cite
|
Sign up to set email alerts
|

Opioid stimulation in the ventral tegmental area facilitates the onset of maternal behavior in rats

Abstract: This research investigated the effect of an increase or decrease in opioid activity in the ventral tegmental area (VTA) on the onset of maternal behavior in rats. In Experiment 1, the latency to show maternal behavior toward foster rat pups (sensitization latency) was determined in maternally naive female rats given either nothing or a unilateral intra-VTA injection of morphine sulfate (MS) (0.0, 0.01, 0.03, 0.1 or 0.3 J.Lg), on the first three days of a lO-day period' of constant exposure to pups. Rats treate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 74 publications
1
30
0
Order By: Relevance
“…2 and 3). Overall, these findings replicated those of Thompson and Kristal (1996): a dose of 0.03 μg morphine, injected into the VTA facilitates the onset of maternal behavior, but a dose of 0.01 μg of morphine does not. The individual infusion groups were then compared across morphine doses.…”
Section: Resultssupporting
confidence: 68%
See 4 more Smart Citations
“…2 and 3). Overall, these findings replicated those of Thompson and Kristal (1996): a dose of 0.03 μg morphine, injected into the VTA facilitates the onset of maternal behavior, but a dose of 0.01 μg of morphine does not. The individual infusion groups were then compared across morphine doses.…”
Section: Resultssupporting
confidence: 68%
“…Discussion Thompson and Kristal (1996) showed that VTA microinjection of 0.03 μg and 0.1 μg, but not of 0.01 μg morphine facilitates the onset of maternal behavior. The present study confirmed that 0.03 μg morphine, but not 0.01 μg morphine, injected into the VTA, shortens the latency to onset of maternal behavior in naïve virgins.…”
mentioning
confidence: 90%
See 3 more Smart Citations